Long-term effectiveness of an educational and physical intervention for preventing low-back pain recurrence: a randomized controlled trial - Emmanuelle Chaléat-Valayer; Angélique Denis; Kariman Abelin-Genevois; Amélie Zelmar; Fabienne Siani-Trebern; Sandrine Touzet; Alain Bergeret; Cyrille Colin; Jean-Baptiste Fassier (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
OBJECTIVE: Low-back pain (LBP) is a common and recurrent condition, but the evidence is scarce about effective strategies to prevent recurrence and disability in the longer term. This study investigated the effect of a light exercise program, initiated in the workplace and continued at home, in reducing recurrence of LBP episodes among healthcare workers. METHODS: A total of 353 healthcare workers from ten hospitals were enrolled in a randomized controlled trial (RCT) and were randomized to the intervention or control groups, the latter of which received usual care. The intervention comprised three steps: (i) a 2-hour education session, (ii) five weekly 90-minutes exercise training sessions in the workplace, and (iii) a home-based self-managed exercise program. The main outcome was recurrence of LBP with sick-leave at 24-months follow-up. RESULTS: At two-year follow-up, 35 workers (24%) in the intervention group and 31 workers (21%) in the control group had at least one LBP recurrence with sick leave. No effect was observed between groups [odds ratio (OR) 1.22, 95% confidence interval (95% CI) 0.67-2.23, P=0.516]. The intervention was effective in reducing fear avoidance with a mean reduction of -3.6 (95% CI -4.8- -2.4) points on the fear-avoidance beliefs questionnaire score for physical activity (FABQ-P) in the intervention group compared with -1.3 (95% CI -2.2- -0.3) points in the control group (P<0.05). It was also effective in improving muscle endurance with a mean increase of 13.9 (95% CI 3.3-24.5) minutes on the Sorensen test in the intervention group compared with -8.3 (95% CI-17.5-0.9) minutes in the control group (P<0.05). Healthcare utilization was reduced in the intervention group for painkillers, medical visits, imaging and outpatient physiotherapy. CONCLUSION: It was not possible to conclude about the effectiveness of a light exercise program to reduce LBP recurrence episodes in the long-term in healthcare workers. However, it was effective to improve muscle endurance, and to reduce fear-avoidance beliefs and healthcare utilization. Further studies are necessary in order to identify effective interventions to reduce LBP recurrence and related sick-leaves.